Adaptation and development of process integration tools for an existing iron ore pelletising production system - Sandberg, Johan; Dahl, Jan (Luleå tekniska universitet, Energivetenskap, 2008)
Energy consumption has been in focus in the mining industry for some time and efforts to optimise the energy consumption in individual process steps have been made with fairly good results. However, until now process integration techniques has been sparsely utilised. In this paper a project aimed to develop and apply process integration techniques for the processing units of a magnetite based iron ore upgrading plant producing mainly iron ore pellets is described. The iron ore upgrading system in focus within this research project is the LKAB facilities in Kiruna in the north of Sweden. A brief introduction of the iron ore upgrading system of LKAB in Kiruna is given. The background problem is formulated and an overview of MIND/reMIND, the main methods and tools to be used in the project are described. Finally, some of the main focus areas of the optimisation are discussed. The paper ends with some closing statements regarding the current status of the project and the future work. Godkänd; 2008; 20080917 (josa)